2012
DOI: 10.3109/1061186x.2012.722639
|View full text |Cite
|
Sign up to set email alerts
|

PEG conjugation of a near-infrared fluorescent probe for noninvasive dual imaging of lung deposition and gene expression by pulmonary gene delivery

Abstract: Dual imaging of lung deposition and gene expression following the pulmonary delivery of a gene formulation is useful for a precise analysis of gene transfection efficiency in vivo. As a novel probe for evaluating lung deposition, in this study, a poly(ethylene glycol)-conjugated near-infrared fluorescent probe (PEG-NIRF) was newly synthesized, and compared with indocyanine green (ICG), for application to pDNA/polyethyleneimine (PEI) complex. PEG-NIRF had superior characteristics including a larger Stokes shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this study, we prepared conventional gel formulations with a fluorescent drug to investigate the fate of the drug after administering them intra-articularly. We traced the fate of indocyanine green (ICG), which is clinically used as an agent for liver/circulatory function tests and has also been used in pharmacokinetic studies as a fluorescent substance in laboratories, 7) after intraarticular administration in rats. ICG is highly soluble in water and is suitable as a tracer by fluorescence imaging.…”
mentioning
confidence: 99%
“…In this study, we prepared conventional gel formulations with a fluorescent drug to investigate the fate of the drug after administering them intra-articularly. We traced the fate of indocyanine green (ICG), which is clinically used as an agent for liver/circulatory function tests and has also been used in pharmacokinetic studies as a fluorescent substance in laboratories, 7) after intraarticular administration in rats. ICG is highly soluble in water and is suitable as a tracer by fluorescence imaging.…”
mentioning
confidence: 99%
“…It should be noted that many other biocompatible, water soluble and biodegradable polymers have been developed as in vivo imaging probes 58 . For example, Poly(ethylene glycol) 59 , Poly (L-glutamic acid) 60 and N-(2-Hydroxypropyl) methacrylamide 61 with various functional groups have been used to fabricate probes with different targeting and therapeutic moieties. It is possible the FR-targeting probes can be made using different polymer carriers.…”
Section: Discussionmentioning
confidence: 99%
“…A lung deposition and gene expression correlation study found that after 60 minutes, target gene expression was significant. 44 This study therefore highlights the importance of using a heptamethine dye, as opposed to an ICG dye, for improved antitumor efficacy when using a gene delivery strategy.…”
Section: Cancer Therapy Using Heptamethine Nirf Nanocomplexesmentioning
confidence: 93%